From Pegon to Arabic: The New Tafsir of Indonesian Pesantren - Anam, Saichul; Nabil Iklil Mubarok , Muhammad (Aqwal: Journal of Qur'an and Hadis Studies, 2025)
Background and Objectives: This article examines the epistemological shift in the tradition of Qur’anic exegesis within Indonesian pesantren in the 21st century, marked by the transition from the use of Pegon script—a localized adaptation of the Arabic script—toward the production of tafsir texts in formal Arabic (fushah). Historically, Pegon functioned not only as a tool for religious instruction but also as a cultural symbol of epistemic autonomy. However, growing engagement with global Islamic scholarly networks has prompted pesantren scholars to reconfigure their knowledge production practices. Methods: This study aims to investigate the symbolic and epistemic dimensions of this transformation in order to understand the evolving position of pesantren within the transnational landscape of Islamic knowledge. Utilizing Norman Fairclough’s model of Critical Discourse Analysis (CDA), the research analyzes four contemporary tafsir texts composed within the pesantren tradition: Safīnah Kallā Saya’lamūn, Hidayatul Qur’an, Firdaus al-Na’im, and Risālah al-Mūjizah. Main Findings: the use of formal Arabic serves not only as a means of communication but also as an epistemic strategy to reaffirm continuity with classical Islamic scholarship while achieving legitimacy within modern academic contexts. These tafsir texts adopt conservative exegetical methods yet are presented in formats aligned with global academic standards. Contribution: this study lies in its demonstration of how contemporary pesantren tafsir embodies an ongoing negotiation between local identity, traditional authority, and the demands of transnational Islamic scholarly discourse. Conclusion: This transformation highlights the pesantren’s active role in reshaping Islamic epistemology in the global era.